Synergistic process using calcium peroxide and ferrous iron for enhanced ultrafiltration of Microcystis aeruginosa-laden water. (1st March 2022) - Cheng, Xiaoxiang; Hou, Chengsi; Gao, Hongbo; Li, Peijie; Zhu, Xuewu; Luo, Congwei; Zhang, Lijie; Jin, Yan; Wu, Daoji; Liang, Heng
Highlights: CaO2 /FeSO4 was proposed for enhanced ultrafiltration of algae-laden water. The agglomeration of algal foulants was significantly promoted by CaO2 /FeSO4 . The synergistic effect of CaO2 and FeSO4 effectively alleviated membrane fouling. The accumulation of pollutants on the membrane surface was reduced. The in-situ formed Fe 3+, OH, and Ca(OH)2 contributed to the beneficial effect. Abstract: Algal blooms and eutrophication in natural surface water not only pose a threat to human health, but also adversely affect the water purification process. Ultrafiltration (UF) has been proved to be effective for the retention of algal cells, but its further application is still restricted by the relatively limited removal of algal organics and membrane fouling. To enhance the UF performance, a synergistic process using calcium peroxide and ferrous sulfate (CaO2 /FeSO4 ) was proposed for the treatment of Microcystis aeruginosa -laden water. The results suggested that the removal of algal cells and organics, fluorescent components were effectively increased with the synergism of CaO2 and FeSO4 . The particle size distribution and morphology revealed that the size of algal pollutants apparently increased due to the formation of algal flocs. With CaO2 /FeSO4 pretreatment, the terminal specific flux of polyethersulfone and polyvinylidene fluoride membranes were increased by 75.0% and 56.5%, individually. The fouling resistances were significantly reduced, and the fouling mechanism transition to cake filtration was delayed. The membrane interface properties including morphologies and functional groups were characterized, further verifying the effectiveness. The in-situ formed Fe 3+ integrated with Ca(OH)2 showed excellent coagulation effect, thus promoting the agglomeration of algal foulants. Simultaneously, the generated hydroxyl radical could improve the oxidative degradation of algal organics. In conclusion, the CaO2 /FeSO4 strategy has great advantages and application prospects in enhancing UF performance for Microcystis aeruginosa -laden water treatment. Graphical abstract: Image, graphical abstract